Pengembangan Permainan BOGO (Bola Tangan & Gobak Sodor) untuk Peserta Didik Sekolah Dasar Kelas Atas di SD Kecamatan Tanjunganom Kabupaten Nganjuk - Hardiyanto, Lucky Prasetyo; Herpandika, Reo Prasetiyo; Pratama, Budiman Agung (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to develop a handball game, by collaborating between handball and the traditional gobak sodor game that is already known by students under the name "BOGO Game", which is used as a medium for learning handball for upper elementary school students. The method used is Research and Development (R&D) with a simplified development model by the Puslitjaknov Team. Data collection was carried out through observation, interviews, and distributing questionnaires. The small-scale test involved 50 students from three schools, while the large-scale test involved 150 students from ten elementary schools in Tanjunganom District, Nganjuk. The results of the large-scale test from material experts, media, and academics showed a percentage of feasibility of 100%, 93%, and 93.33%, respectively. From practitioners and students in the large-scale test also showed a percentage of 85.89% and 88.93% overall in the "Very Good" category. Based on these results, the "BOGO game” was declared very feasible to be used in handball learning.